2005
DOI: 10.1007/s11661-005-0180-6
|View full text |Cite
|
Sign up to set email alerts
|

The strain rate effect of an open cell aluminum foam

Abstract: The dynamic compressive behavior of an open-cell commercially pure aluminum foam was experimentally investigated with a split Hopkinson bar (SHPB) and numerically simulated using the finite element (FE) method. It is found that the flow stress increases with increasing strain rate, demonstrating the existence of strain rate dependence in the present aluminum foam. This dependence is believed to originate from the polygonal pore architecture, the relatively high density, the intrinsic property of aluminum, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…A limited rate sensitivity is found for Alporas foam and honeycomb, which is mainly due to inertia effects in the successive buckling of the cell walls (Zhao and Abdennadher, 2004;Han et al, 2005). Nickel hollow spheres exhibit also a rate sensitivity that is believed to be due to the rate sensitivity of the cell wall material.…”
Section: Discussionmentioning
confidence: 99%
“…A limited rate sensitivity is found for Alporas foam and honeycomb, which is mainly due to inertia effects in the successive buckling of the cell walls (Zhao and Abdennadher, 2004;Han et al, 2005). Nickel hollow spheres exhibit also a rate sensitivity that is believed to be due to the rate sensitivity of the cell wall material.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there exists a zone where the material ''particle velocity", ''stress" and ''strain" are discontinuous when the crushing velocity exceeds a critical value and that the one-dimensional shock theory tends to overestimate slightly the crushing stress and energy absorbed. In this paper, considering the structural features of hexagonal-cell honey- Han et al (2005) comb, a relatively precise definition of the ''particle" velocity, local engineering strain and engineering stress is introduced to illustrate the plateau stress and the total dissipated energy. It is very useful and explicit to know the engineering stress and strain field in the whole honeycomb along the loading direction.…”
Section: Introductionmentioning
confidence: 99%
“…In general terms, the rate sensitivity of cellular metals may be affected by micro-inertia [9,[23][24][25]; rate sensitivity of cellwall material [24,26,27]; compression of entrapped gas in cells [6,11]; and other factors, such as inertia and shock wave effects [28] that may change the deformation mode of the material. Su et al [22] suggested that, given the "flat topped" quasi-static stress versus strain curve of aluminum foams, micro-inertia plays little role under dynamic loading [10].…”
Section: Resultsmentioning
confidence: 99%